(3+2)-Cycloaddition Reactions of Oxyallyl Cations - Li, Hui; Wu, Jimmy (Synthesis, 2015)
The (3+2)-cycloaddition reaction involving oxyallyl cations has proven to be a versatile and efficient approach for the construction of five-membered carbo- and heterocycles, which are prevalent frameworks in natural products and pharmaceuticals. The following article will provide a brief summary of recent disclosures on this process featuring chemo-, regio- and diastereoselective oxyallyl cycloadditions with both electron-rich and electron-deficient 2π partners.1 Introduction2 Heteroatom-Substituted Oxyallyl Cations3 Oxyallyl Cations Derived from Substituted Ketones4 Oxyallyl Cations Intercepted from Nazarov Cyclization5 1-Alkylidene-2-oxyallyl Cations6 Summary and Outlook
Keywords: cycloaddtion; oxyallyl cation; heterocycles; regioselectivity; diastereoselectivity